2014
DOI: 10.1182/blood-2013-01-477620
|View full text |Cite
|
Sign up to set email alerts
|

Targeting components of the alternative NHEJ pathway sensitizes KRAS mutant leukemic cells to chemotherapy

Abstract: Key Points• Oncogenic KRAS causes upregulation of components of the alt-NHEJ pathway, thereby promoting genomic instability.• Inhibition of the alt-NHEJ pathway selectively sensitizes KRAS-mutant leukemic cells to cytotoxic agents.Activating KRAS mutations are detected in a substantial number of hematologic malignancies. In a murine T-cell acute lymphoblastic leukemia (T-ALL) model, we previously showed that expression of oncogenic Kras induced a premalignant state accompanied with an arrest in T-cell differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
(54 reference statements)
2
41
0
Order By: Relevance
“…GEMA, with emphasis on gene mutation analysis, may also be applied to identify additional oncogenes that sensitize cells to PARP1 inhibitor treatment, for example TMPRSS2-ERG-positive prostate carcinomas (DNA-PKcs deficiency), EGFR mutant-positive lung carcinomas (Fanconi anemia deficiency), EWSR1-FLI1-positive Ewing's sarcomas, and KRAS mutant-positive leukemias (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…GEMA, with emphasis on gene mutation analysis, may also be applied to identify additional oncogenes that sensitize cells to PARP1 inhibitor treatment, for example TMPRSS2-ERG-positive prostate carcinomas (DNA-PKcs deficiency), EGFR mutant-positive lung carcinomas (Fanconi anemia deficiency), EWSR1-FLI1-positive Ewing's sarcomas, and KRAS mutant-positive leukemias (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that mutant Ras expression confers heightened DNA repair capability through the upregulation of CUX1, which functions in BER as an ancillary factor that stimulates the activity of the OGG1 DNA glycosylase (23). Another study found that inhibition of the alt-NHEJ pathway selectively sensitized KRAS mutant leukemic cells to cytotoxic agents (24). Mutant K-Ras was shown to activate alt-NHEJ by upregulating DNA ligase III, poly (ADP-ribose) polymerase 1 (PARP1), and XRCC1.…”
Section: Introductionmentioning
confidence: 99%
“…As is reported, ATM is a protein kinase that phosphorylates several key proteins involved in the DDR. It can be activated by its autophosphorylation at Ser1981 position [20], and it can also phosphorylate its downstreams of ATR, BRCA1, and RAD51 to activate the HR DNA repair [19,31], so we speculated that the inhibition of p-ATM, p-ATR, p-BRCA1, and p-RAD51 may be ascribed to ATM inhibition. To further identify whether INPP4B-mediated DNA repair is ATMdependent or not, we then evaluated the influences of KU55933 and Chloroquine on INPP4B knockdown-induced sensitizing effect on cytarabine treatment.…”
Section: Discussionmentioning
confidence: 98%
“…p-H2AX is a well-known maker of DNA double-strand breaks, H2AX is phosphorylated at the sites of DSBs and the level of p-H2AX has been shown to give a sensitive and accurate estimation of the number of DSBs within DNA. The presence of p-H2AX in chromatin can be detected shortly after induction of DSBs in the form of discrete nuclear foci [20]. To explore if the difference of this cell viabilities is associated with the distinction of DSBs formation, then we detected the p-H2AX expression between KG-1 and HL60 cells after cytarabine treatment, and observed p-H2AX expression is higher in HL60 than KG-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation